Virtual reality for pain management: an umbrella review - Viderman, Dmitriy; Tapinova, Karina; Dossov, Mukhit; Seitenov, Serik; Abdildin, Yerkin G. (Frontiers in Medicine, 2023)
Background and objective Virtual reality is a promising pain control strategy for various pain conditions. This umbrella review of systematic reviews and meta-analyses aims to evaluate the analgesic effects of virtual reality. Methods We searched for the relevant reviews in Scopus, PubMed and Cochrane library. Our primary outcome was pain, with secondary outcomes including disability, general health status, patient satisfaction, depression, balance, fear of movement, and adverse events. The quality of included articles was evaluated using the AMSTAR-2 tool. Results 21 systematic reviews and meta-analyses with 274 studies and 17,680 patients were included in this review. All the reviews concluded benefits of virtual reality in managing pain conditions, including chronic and pain. Discussion and conclusions This umbrella review demonstrates successful application of virtual reality in pain control, including perioperative, periprocedural, and chronic pain settings. Virtual reality can be used as an alternative therapy for pain management in children and adults.